Light-Responsive Actuators Based on Graphene - Gao, Yuan-Yuan; Han, Bing; Zhao, Wen-Ya; Ma, Zhuo-Chen; Yu, Yong-Sen; Sun, Hong-Bo (Frontiers in Chemistry, 2019)
As a typical 2D carbon material, graphene that possesses outstanding physical/chemical properties has revealed great potential for developing soft actuators. Especially, the unique properties of graphene including the excellent light absorption property, softness and thermal conductivity play very important roles in the development of light-responsive graphene actuators. At present, various light-driven actuators have been successfully developed based on graphene and its derivatives. In this minireview, we reviewed the recent advances in this field. The unique properties of graphene or graphene-related materials that are of benefit to the development of light-driven actuators have been summarized. Typical smart actuators based on different photothermal/photochemical effects, including photothermal expansion, photothermal desorption, photoisomerization and photo-triggered shape memory effect, have been introduced. Besides, current challenges and future perspective have been discussed. The rapid progress of light-responsive actuators based on graphene has greatly stimulates the development of graphene-based soft robotics.